The Application of Quantum Learning Interactive Multimedia Assisted Learning Model towards the Student’s Learning Outcomes in Animalia Material - Afniyati, Nur; Yuniastuti, Ari; Subekti, Niken (FMIPA UNNES, 2018)
Observation was done to biology teachers and students in MAN 2 Semarang, so that students have not experienced difficulty of learning the Animalia material. The less of media and facilities make students' motivation low, so it impacts on learning outcomes. The classical completeness average of daily tests on the material value of invertebrates is less than 60% with a minimum completeness criteria (KKM) is 75. The model can be used in providing an understanding of Animalia matter is learning Quantum Learning. The Quantum Learning is learning to use a syntax TANDUR (Tandur/Grow, Alami/Natural, Namai/ Name, Demonstrasikan/Demonstrate, Ulangi/Repeat, Rayakan/Celebrate). The research was conducted in MAN 2 Semarang with the research method used Pre-Eperimental, One Shot Case Study. The research design used in this research is quantitative 1q. The research steps include making proposals and instruments, testing trial and feasibility, instrument validation, application of learning method and end data processing. The results are cognitive and psychomotor learning outcomes. The cognitive learning outcomes showed the classical completeness of experimental class 95% and 90%, the average value of class X IPA 1 85 and 80. Psychomotor learning outcomes showed the experimental class average 82 and 81 with good criteria. Based on the data obtained indicates that the method applied is effective to maximize the learning outcomes. The learning outcome is effective when classical learning completeness reached ≥75% of the total and ≥75% for psychomotor aspect. Therefore, according to the results of this study, it can be concluded that the application of Quantum Learning- assisted Interactive Multimedia learning model towards student’s learning outcomes in Animalia material on SMA / MA and teachers give a positive response to the applied learning. Further, it can be imlied that Quantum Learning-assisted interactive multimedia learning model effect on student learning outcomes.